Granulocyte function in response to acute alcohol consumption: temporal shifts from proinflammatory activation to antiinflammatory modulation in healthy volunteers - Sturm, Ramona; Haag, Florian; Rinderknecht, Helen; Bülow, Jasmin Maria; Wagner, Nils; Zabel, Julian; Bergmann, Christian B; Marzi, Ingo; Relja, Borna (Journal of leukocyte biology, 2025)
While chronic alcohol use is proinflammatory, the immune effects of acute intake remain unclear. We examined granulocyte responses to binge drinking, common in youth. Twenty-two volunteers consumed 12 alcoholic drinks over 4 h (blood alcohol concentration 1.0‰). Blood was collected at baseline (T0), 2 h (T2), 4 h (T4), 6 h (T6), 24 h (T24), and 48 h (T48) postintake. Interleukin (IL)-6 and M30 (inflammation, cell death) were analyzed by enzyme-linked immunosorbent assay; CXCL10 and MPO gene expression in polymorphonuclear leukocytes (PMNLs) by qRT-PCR; CD62L and Toll-like receptor (TLR4) on CD16+ granulocytes by flow cytometry; inflammasome activation post-LPS/ATP stimulation; and PMNL adhesion to A549 lung cells. IL-6 increased significantly at T2 to T6; M30 peaked at T4, decreasing at T24 and T48. CXCL10 and MPO increased at T2 and T4; MPO declined at T24 and T48. TLR4-positive granulocytes increased at T2 and T4. Active caspase-1 rose over 48 h, while stimulated activation declined at T4 and T24. CD62L increased at T2 before declining. PMNL adhesion decreased significantly at T24 and T48. Acute alcohol triggers early inflammation followed by immune suppression.
Online veröffentlicht: 6. Juni 2025
Gesehen am 12.09.2025